2017
DOI: 10.1038/s41559-017-0297-1
|View full text |Cite|
|
Sign up to set email alerts
|

Intermediate degrees of synergistic pleiotropy drive adaptive evolution in ecological time

Abstract: Rapid phenotypic evolution of quantitative traits can occur within years, but its underlying genetic architecture remains uncharacterized. Here we test the theoretical prediction that genes with intermediate pleiotropy drive adaptive evolution in nature. Through a resurrection experiment, we grew Arabidopsis thaliana accessions collected across an 8-year period in six micro-habitats representative of that local population. We then used genome-wide association mapping to identify the single-nucleotide polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
229
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 114 publications
(244 citation statements)
references
References 63 publications
15
229
0
Order By: Relevance
“…thaliana (Brachi et al ., , ); and (iii) by demonstrating the in situ adaptive evolution of a highly genetically polymorphic local population of A . thaliana to increased interspecific competition in less than eight generations (Frachon et al ., ). Therefore, A .…”
Section: The Genetics Of Natural Variation Of Plant–plant Interactionsmentioning
confidence: 97%
See 4 more Smart Citations
“…thaliana (Brachi et al ., , ); and (iii) by demonstrating the in situ adaptive evolution of a highly genetically polymorphic local population of A . thaliana to increased interspecific competition in less than eight generations (Frachon et al ., ). Therefore, A .…”
Section: The Genetics Of Natural Variation Of Plant–plant Interactionsmentioning
confidence: 97%
“…We therefore argue that identifying genes that underlie natural variation of plant–plant interactions under natural conditions will be crucial for understanding the adaptation to the presence of neighbors, especially in wild species. Accordingly, a recent study reported for the first time (to our knowledge) a GWA mapping approach combined with an in situ phenotyping experiment of heterospecific interactions (Frachon et al ., ). In this study, 195 whole‐genome sequenced natural accessions collected in a highly genetically polymorphic local population of A .…”
Section: The Genetics Of Natural Variation Of Plant–plant Interactionsmentioning
confidence: 97%
See 3 more Smart Citations